Hubungan Perilaku Merokok Keluarga dengan Kejadian Bronkopneumonia pada Balita: The Relationship between Family Smoking Behavior and the Incidence of Bronchopneumonia in Toddlers - Esti Dwi Apriliani; Akbar Amin Abdullah; Feri Catur Yuliani (Universitas Ngudi Waluyo, 2026)
Bronchopneumonia is one of the leading causes of death in young children worldwide, including in developing countries. Smoking behavior within the family environment also increases the incidence of this disease. The research aims to determine the relationship between family smoking behavior and the incidence of bronchopneumonia in toddlers. The research method is quantitative correlational with a cross-sectional approach. A sample of 46 toddlers was selected using purposive sampling. The research was conducted in the children's room of RSI Sultan Hadlirin Jepara. The instrument consists of a smoking behavior questionnaire and medical record data on the occurrence of bronchopneumonia. The analysis uses the Chi-Square test with signification 5%.. The research findings showed that 47.8% of children had severe smoking behavior and 95.7% experienced bronchopneumonia. Analysis revealed a significant relationship between family smoking behavior and the occurrence of bronchopneumonia in toddlers, with a p-value of 0.003. The conclusion is that family smoking behavior increases the risk of bronchopneumonia in toddlers. Further research is needed on other factors related to the development of bronchopneumonia.